A combination of linalool and linalyl acetate synergistically alleviates imiquimod-induced psoriasis-like skin inflammation in BALB/c mice - Rai, Vineet Kumar; Chanda, Debabrata; Chanotiya, Chandan Singh; Yadav, Narayan Prasad (Frontiers in Pharmacology, 2022)
Introduction: Psoriasis is a chronic inflammatory skin disorder, that is characterized by keratinocytes hyperproliferation and differentiation with increased immune cell infiltration. The anti-psoriatic effect of lavender oil has been reported. However, its phytoconstituents linalool (L) and linalyl acetate (LA) showed distinctive affinity with psoriasis targets. Objectives: This investigation was aimed to find out the combined effect of L and LA, in the amelioration of psoriasis like skin inflammation and safety in long-term topical uses. Methods: The combined effect of L and LA was compared with their individual effects. The anti-psoriatic activity was done using imiquimod (IMQ) induced psoriasis in BALB/c mice and evaluated to reduce in PASI and CosCam scores and Th-1 and Th-17 cell-specific cytokines levels. The acute and repeated dose dermal toxicities were investigated as per the OECD guidelines. Results: L and LA combination (LLA) in 1:1 w/w ratio at 2% concentration showed a synergistic effect. The combination showed 76.31% and 71.29% recovery in PASI and CosCam Scores, respectively however L2% and LA2% showed 64.28% and 47.61% recovery in PASI scores, respectively and 64.75 and 56.76% recovery in CosCam scores, respectively. It showed >90% and >100% recovery in Th-17 and Th-1 cell-specific cytokines, respectively and restored epidermal hyperplasia and parakeratosis toward normal when compared with psoriatic mice. A marked reduction in NF-κB, ccr6, and IL-17 expression was also observed in LLA treated group. This combination was observed to be safe on therapeutically effective dose for 28 days as no significant change was observed in organ and body weights, liver and kidney parameters along with differential leukocyte counts. Conclusions: This study proves the synergy between L and LA in 1:1 w/w ratio at 2% in the treatment of psoriasis like skin inflammation and provides strong scientific evidence for its safe topical use.